AMAPACHANA PROPERTY OF SUNTHI (ZINGIBER OFFICINALE ROXB) IN RAISED ESR ASSOCIATED WITH AMAVATHA- A CLINICAL STUDY (AYUSHDHARA, 2017)
Amavatha is a disease caused due to the vitiation or aggravation of Vayu associated with Ama. Vitiated Vayu circulates Ama all over the body through Dhamanies and takes shelter in Sleshmastana (Amasaya, Sandhi etc), producing symptoms such as stiffness, swelling and tenderness in small and big joints. The symptoms of Amavatha are identical to rheumatoid arthritis and in common clinical practices it can be observed that there will be raised ESR value in conditions like Rheumatoid arthritis due to chronic inflammation. As and when the inflammation aggravates due to Ama, the ESR value does not come to the normal level. Various drug trials were already carried out on Amavatha, yet there is a lacuna in the management of Amavatha. As Pachana is considered as the first and for most treatment of Amavatha. A research was conducted to find out the Amapachana property of Sunthichurna in raised ESR associated with Amavatha. 30 patients were randomly selected from the outpatient department of Dravyagunavijnana, Govt Ayurveda college, Thripunthura. 2gm of Sunthi churna in divided dose were given to the patients before food with luke warm water as Anupana for 30 days. The result showed significant decline in the severity of subjective symptoms like Angamarda (Pain on body parts), Aruchi (Anorexia), Alasya (Lethargy), Gourava (Heaviness), Apaka (Indigestion) and Sopha (Oedema) and there is a mild decrease in the value of ESR. The study revealed that the trial drug is effective in case of Amavatha.